Transformasi Simbol dan Pergeseran Identitas yang Bergeser: Sebuah Studi Antropologi Budaya tentang Rimpu dan Hukum Islam dalam Masyarakat Bima - Mujahidin, Mujahidin; Naping, Hamka (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This article aims to analyze how the Bima community interprets and reconstructs the Rimpu tradition as a cultural symbol intersecting with Islamic law, to identify the various forms of practice, modification, and contestation of Rimpu within social life and digital spaces, and to examine how Rimpu adapts amid contemporary modernization. The study employs a qualitative approach using ethnographic methods—including participant observation, in-depth interviews, and documentation—to produce a detailed and comprehensive account of this socio-cultural phenomenon. The findings reveal that Rimpu functions as a symbol of morality and honor as well as a mechanism of social control rooted in the Maja Labo Dahu value system of Bima society. Rimpu constitutes part of a cultural habitus reproduced through socialization processes within families and communities. A significant shift has occurred from collective obligation to individual choice, accompanied by the commodification of Rimpu within the cultural economy—particularly through festivals and creative industries, including rimpu cili for young girls and rimpu colo for adult women—now featured in cultural parades, local beauty contests, and public performances as a visual representation of Bima identity. This transformation reflects an ongoing negotiation between Islamic values, cultural identity, and the forces of modernity. The article recommends that local government strengthen sustainable cultural preservation programs, support local culture-based MSMEs and creative industries, and integrate cultural education into the formal education system.